1983
DOI: 10.1084/jem.157.6.1920
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of natural antiallotype antibody responses by idiotype network-induced auto-antiidiotypic antibodies.

Abstract: This study was designed to determine whether natural immune responses could elicit immunoregulatory auto-antiidiotypic antibodies. Female rabbits heterozygous at the a and b Ig loci were bred to homozygous males. Offspring of one such breeding were studied for natural production of antibodies specific for the noninherited allotypes and for the production of immunoregulatory auto-antiidiotypic antibodies. All offspring mounted natural antiallotype responses. The anti-a1 responses cycled as a function of time wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…For dc 10-3, these peaks typically correspond to periods between 30 and 150 days. This is in agreement with empirical data of Rodkey & Adler (1983) which shows an 80-day period in rabbits. Networks with larger rates of complex formation failed to have sustained oscillatory behavior.…”
Section: Periodssupporting
confidence: 93%
“…For dc 10-3, these peaks typically correspond to periods between 30 and 150 days. This is in agreement with empirical data of Rodkey & Adler (1983) which shows an 80-day period in rabbits. Networks with larger rates of complex formation failed to have sustained oscillatory behavior.…”
Section: Periodssupporting
confidence: 93%
“…Figure 11 a shows that under quite reasonable parameter choices the system can undergo sustained oscillations with the concentrations of idiotypic and anti-idiotypic antibodies fluctuating inversely with a period of approximately 80 days. These oscillations are reminiscent of those found by Rodkey & Adler (1983) in a year-long study of naturally induced auto-antiidiotypic antibodies in the rabbit, in which one could also identify peaks separated by 80 d. The oscillations found by Rodkey & Adler were much more irregular than those in Fig. lla.…”
Section: Al +S2b2^aj'b2-supporting
confidence: 68%
“…lib). Figs 2 and 4A of Rodkey & Adler (1983) show similar peaks at similar times (d 120 and 260, and 200 and 280, respectively). Inverse idiotypic and anti-idiotypic fluctuations have also been found by Kelso & Cerny (1979) and Bona (1982).…”
Section: Al +S2b2^aj'b2-mentioning
confidence: 61%
“…Studies in rabbits and mice have shown that maternal IgG antibodies can both augment and suppress neonatal responsiveness (Okamoto et al, 1989;Rodkey and Adler, 1983;Rubinstein et al, 1982;Wikler et al, 1980). The suppression of IgE responsiveness is noteworthy (Bednar-Tantscher et al, 2001;Jarret and Hall, 1979;Roberts and Turner, 1983), which might explain the delayed onset of atopy among breastfed infants (Halpern et al, 1973).…”
Section: Immunomodulation By Passive Igs and Antibodiesmentioning
confidence: 99%